Réformer l’hôpital comme une entreprise. Les errements de trente ans de politique hospitalière (1983-2013) - Jean-Paul Domin (Revue de la Régulation)
This article sets out to understand why, for the last thirty years, hospital reform has met with fierce opposition from staff. Since the late 70s there has been a change in references in the shape of a new way of considering hospitals based on new standards, notably the theory of contracts and the principal-agent theory. This theoretical transformation incites public authorities to experiment with new management schemes favouring doctors’ participation in managing establishments. Indeed, this approach of hospitals clashes with their history and more generally with their founding compromise which developed in the early 19th century.